2004
DOI: 10.1159/000076128
|View full text |Cite
|
Sign up to set email alerts
|

Topical Application of FK506 (Tacrolimus) Ointment Inhibits Mite Antigen-Induced Dermatitis by Local Action in NC/Nga Mice

Abstract: Background: FK506 ointment (tacrolimus ointment, protopic) is a new drug therapeutically effective for patients with atopic dermatitis (AD). However, the mechanism of action of FK506 ointment on AD is not fully understood. Methods: We examined the effect of FK506 ointment on mite antigen-induced dermatitis in NC/Nga mice. Clinical symptoms and ear thickness were recorded, and histopathological studies and in vitro analyses were performed. Results: Topical application of FK506 ointment (0.03–0.3%) suppressed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 16 publications
0
20
1
Order By: Relevance
“…In contrast to the findings of others [9, 16], our results showed rather unexpectedly that neither the NC/Nga nor the BALB/c mice responded to treatment with betamethasone or tacrolimus with a reduction of the cellular infiltrate. In these experiments, challenge and treatment were given at the same time; consequently, the mice may develop an immunological response to the treatment, thus explaining the inflammatory response observed following corticosteroid treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to the findings of others [9, 16], our results showed rather unexpectedly that neither the NC/Nga nor the BALB/c mice responded to treatment with betamethasone or tacrolimus with a reduction of the cellular infiltrate. In these experiments, challenge and treatment were given at the same time; consequently, the mice may develop an immunological response to the treatment, thus explaining the inflammatory response observed following corticosteroid treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…Current topical treatment possibilities for AD are topical corticosteroids as a standard treatment and topical calcineurin inhibitors (macrolide immunosuppressants) such as tacrolimus or pimecrolimus as a second-line therapy [1]. Previously, only spontaneous mouse models of AD have been used to investigate topical drugs in AD [19,20]. Here we show that our mouse model of AD caused by repeated epicutaneous ovalbumin (OVA) and SEB exposures is valuable and repeatable model to test topical drugs in AD.…”
Section: Introductionmentioning
confidence: 85%
“…NC/Nga mouse model has been considered as one of the most valuable mouse model representing human AD [5,18,19]. This model has been used for the evaluation of drug candidates developed for the treatment of AD [20,21]. Previously, we established a modified NC/Nga mouse model and suggested that this model might be a useful tool to evaluate drug candidates of AD [16].…”
Section: Discussionmentioning
confidence: 99%